A precarização do trabalho docente no ensino superior: análise sobre as implicações do trabalho do professor designado na Universidade do Estado de Minas Gerais - Francklin, Adelino (Universidade Federal de São Carlos, 2021)
The State University of Minas Gerais (UEMG) has had a high number of temporary professors. This research asks: what are the implications of temporary hiring for teaching work at UEMG, Unidade Passos? The objective of the thesis is to analyze the implications of the process of precarious work of temporary teachers at UEMG, Unidade Passos, in the context of the unfolding of neoliberal educational policies, having as reference the concepts of field, habitus and scientific capital, by Pierre Bourdieu. The study is qualitative and uses bibliographic, documentary and field sources. The bibliographic sources were obtained through the website of SciELO journals, Google Scholar, Rede Universitas.Br and the library of the Federal University of São Carlos (UFSCar). Two notices of simplified selection processes (PSS) from UEMG, published in the years 2018 and 2019, were analyzed for the Passos unit. And semi-structured interviews were carried out with 10 professors from UEMG, Passos unit, transcribed by the researcher. For the analysis of the results, the data triangulation technique and the content analysis technique were used. The hypotheses have been partially confirmed. It was not possible to confirm whether the professional habitus of professors appointed in the face of struggles in the scientific field has undergone significant changes. As for the other hypotheses, we confirm that: a) the maintenance of the high number of positions of professors appointed at UEMG is due to the option of the state government to save with the payroll of public servants; b) the maintenance of designated professors causes greater losses for the development of research and extension and the exercise of functions that refer to management; c) the uncertainty regarding the classification in the PSS for the following year becomes an obstacle for the elaboration and approval of new projects, negatively affecting their academic production due to the difficulty of obtaining scholarships and project continuity; d) teaching is also impaired due to the disincentive to prepare good classes. Several elements were found that confirm the precariousness of teaching work, modifying their practices and being able to cause changes in professional habitus, such as low remuneration; job instability; teacher turnover; high number of didactic charges and teaching duties; having to teach disciplines without adherence with their training and preparation of projects in the short term. There is a high rate of teachers who occupy positions with a partial work regime. Participation in UEMG's PSS annually or every two years, causes uneasiness and disputes in the field, to be experienced among teachers. The continuing education of appointed teachers is negatively affected by instability in positions, given that they do not have the right to leave the position for studies. The expansion in the number of UEMG units, increasing the number of students and teachers, was not accompanied by a proper budget increase. As a result, the infrastructure became precarious, the funds for research, extension and student aid were reduced, the reduction of full-time positions and the maintenance of temporary employment contracts.
The precarization of teaching work in higher education: analysis on the implications of the work of the designated teacher at the University of the State of Minas Gerais
Keywords: Habitus profissional; Precarização; Professores temporários; Universidade do Estado de Minas Gerais (UEMG); Professional habitus; Precarization; Temporary professors; CIENCIAS HUMANAS::EDUCACAO